Religiosity and Subjective Welfare of Women with HIV/AIDS in Surabaya - M. G. Bagus Ani Putra (Psikologia : Jurnal Psikologi, 2015)
This research aims to analyze relation between HIV infection status and religiousness and subjective well being women survivor in Surabaya. The method of this research used interview and questioner toward 28 HIV/AID women survivors in Surabaya. That subjects were selected of 50 women survivors in Surabaya to gain positive HIV diagnosis. In early psychological intervention, we had 30 participants but only 28 participants who attended in medical analysis. Data analysis used statistical test with correlation analysis between psychological and medical variable. As the result, there is a correlation between HIV infection status and religiousness and subjective well being women survivors in Surabaya. It means, if they have a HIV infection status, they have better religiousness and level of subjective well being.